Zoonotic Potential of Brucella microti - Hubálek, Zdenek; Křivanová, Andrea; Nesvadbová, Jiřina; Rudolf, Ivo (Vector borne and zoonotic diseases, 2023)
Background:Brucella microti is a pathogen of rodents and wild mammals. Here, we report the first probable infection with B. microti in a mammalogist. Materials and Methods: In the study, we provided complete clinical description as well as laboratory analysis of probable human infection caused by B. microti. Results: Considering the clinical course of the infection, the obvious epidemiological link (a bite by an infected rodent), the isolation of a pathogen from a sick vole that was affected by clinical infection with B. microti, and the specific serological response (slow agglutination test) in human patient, we can conclude that the human disease described here was probably caused by B. microti, an emerging bacterial pathogen transmitted by rodents. Conclusion: Rodents and other wildlife need to be monitored not only for established zoonotic agents such as hantaviruses, lymphocytic choriomeningitis virus, Leptospira spp., Francisella tularensis, but also for Brucella microti and other atypical rodent-borne brucellae.
Keywords: Animals; Brucella; divoká zvířata; lidé; hlodavci; zvířata; Bacteria; Animals, Wild; Rodentia; Arvicolinae; Humans